The night is dark and full of hesitation. The latest step in the legal trajectory of assisted suicide in Italy: through tentative judicial openings, bioethical contradictions and the Parliament’s deafness - Frati, Paola; Albore, Marco; Ertola, Eleonora Micaela; Del Prete, Sossio; Sorace, Letizia; La Russa, Raffaele; Bolino, Giorgio (Frontiers in Pharmacology, 2025)
The legalization of voluntary assisted dying, or physician-assisted suicide (AS), is gaining momentum as the recognition of a patient’s right to self-determination becomes increasingly integral to medical practice, even in cases involving extreme decisions, such as the cessation of therapy. In Italy, even Law no. 219/2017 already permits to refuse any medical intervention, including life-support treatment (LTS) and with the explicit aim of dying, with no possibility of hindering that choice. Subsequently, two landmark rulings by the Constitutional Court (ordinance no. 207/2018 and judgment no. 242/2019) marked a pivotal moment in legal, bioethical, and clinical discourse, fostering a shift toward a new care paradigm. Nevertheless, these developments remain tentative, reflecting the ongoing legislative gap in this domain. One of the most pressing issues is the restriction of AS to only patients who are dependent on LST thus scotomising a huge base of terminally ill sufferers. Several other significant judicial decisions have also shaped this area, including the Court of Assizes of Massa’s ruling on 27/07/2020, the recent order no. 32/2024 by the GIP of Florence, and the latest Constitutional Court’s 18/07/2024 ruling no. 135, which reaffirmed the previous set-up but also strengthened the validity of the albeit vague, extensive definition of LST formulated in 2020. We also discussed latest opinion of Italian National Committee of Bioethics regarding the definitional boundaries of LST. This article critically examines the concept of LST from clinical, bioethical, and legal perspectives, revealing its inconsistencies as a prerequisite for access to voluntary assistance in dying.